Hubungan Storytelling dengan Kemampuan Bahasa Reseptif Anak PAUD di Kecamatan Jebres Surakarta - Salsabil, Nesa; Susanti, Nadya (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Language is one way of stimulating a child's way of thinking. If a child's language skills are low then it is likely that the child will experience delays in his thinking process. Receptive language development is a complex process in a child's development. Parents can develop their children's receptive language through activities in the form of telling stories, because it can stimulate their language development, especially in the way they think, listen, solve problems and form their character. Storytelling is known to be able to improve children's language skills, because vocabulary will increase when children often listen to stories. Objectives: This research aims to determine the relationship between storytelling and receptive language skills of preschool children in Jebres District Surakarta. Methods: This research uses a quantitative type of research, cross sectional research design. The data collection technique uses purposive sampling. The sample for this research was children aged 2-5 years as many as 65 respondents. The data analysis technique uses the Kendall Tau Test. Results: The results of the research show that there is a relationship between storytelling and receptive language skills of preschool children in Jebres District Surakarta. The significance value is 0.000, which means the p value <0.05 and the r value is 0.511. This shows that the strength of the correlation between the two variables is in the strong category with a positive direction, which means that the higher the storytelling provided, the higher the child's receptive language skills and can increase receptive language skills with a possible percentage of 51.1%. Conclusion: There is a relationship between storytelling and receptive language skills of preschool children in Jebres District Surakarta. Keywords : Receptive Language, Storytelling, Early Childhood